2017
DOI: 10.3892/ol.2017.7049
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of long non‑coding RNA colon cancer‑associated transcript 2 is associated with advanced tumor progression and poor prognosis in patients with colorectal cancer

Abstract: Abstract. The aim of the present study was to explore the clinicopathological and prognostic significance of long non-coding RNA (lncRNA) colon cancer-associated transcript 2 (CCAT2) expression in human colorectal cancer (CRC). Expression levels of lncRNA CCAT2 in CRC, adjacent non-tumor and healthy colon mucosa tissues were detected by quantitative polymerase chain reaction. The disease-free survival and overall survival rates were evaluated using the Kaplan-Meier method, and multivariate analysis was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…In addition, colon cancer patients with high miR-937 expression showed shorter overall survival than those patients with low miR-937 expression. Multivariate Cox regression analysis results also showed lymph node metastasis, vascular invasion, and TNM stage were independent prognostic factors in colon cancer, which is consistent with previous studies [28, 29]. Importantly, multivariate Cox regression analysis results showed miR-937 was an independent prognostic factor in colon cancer.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, colon cancer patients with high miR-937 expression showed shorter overall survival than those patients with low miR-937 expression. Multivariate Cox regression analysis results also showed lymph node metastasis, vascular invasion, and TNM stage were independent prognostic factors in colon cancer, which is consistent with previous studies [28, 29]. Importantly, multivariate Cox regression analysis results showed miR-937 was an independent prognostic factor in colon cancer.…”
Section: Discussionsupporting
confidence: 90%
“…cells, and ZNFX1-AS1 knockdown inhibited cell proliferation. In addition, previous studies have indicated that increased lncRNA-CCAT2 expression may serve as a potential biomarker for CRC diagnosis, and may also serve as an independent predictor of prognosis (36,37). In the present study, CCAT1 expression was significantly upregulated in CRC tissue.…”
Section: Discussionsupporting
confidence: 62%
“…CCAT2 is a 1752 bp lncRNA located on chromosomal region 8q24.21 [288,289,290]. CCAT2 is originally considered as an oncogenic lncRNA in CRC, which is significantly upregulated in CRC tissues and cell lines [279,291,292,293]. In addition, the expression level of CCAT2 in microsatellite-stable (MSS) CRC tissue samples is 10-folds higher than that in microsatellite-unstable (MSI-H) tumors and adjacent normal colon mucosa [291].…”
Section: Lncrnas In Colorectal Cancer (Crc)mentioning
confidence: 99%
“…CCAT2 has also been demonstrated to be associated with other cancers, including GC, BC, NSCLC, and ESCC [288]. A study clarified that a high level of CCAT2 expression in CRC is associated with poor cell differentiation, deep tumor infiltration, increased lymph node metastasis, advanced TNM stage, and short DFS and OS [279,292]. The serum level of CCAT2 expression in CRC patients is suggested to be significantly increased compared with that in controls [294].…”
Section: Lncrnas In Colorectal Cancer (Crc)mentioning
confidence: 99%